China-Risiken stärker beachten - Britta Kuhn (Wirtschaftsdienst, 2023)
– Germany should pay more attention to risks in procurement, manufacturing and sales in China. First, China's population has been shrinking since 2022 and is rapidly ageing; this will cause its economic strength as well as production and consumption opportuni-ties to decrease. Secondly, the threat of a Taiwan invasion is rising and only mitigated by the globally integrated chip industry. Thirdly, China will increasingly shape standards in international payments and Central Bank Digital Currencies. This will raise its power for sanc-tioning other countries financially. Overall, while Germany should focus on further diversifying its economy, its exposure with regard to China is lower than commonly thought.
Keywords: F51; J11; O53; 330; Internationale Wirtschaftsbeziehungen; Bevölkerungsentwicklung; Außenpolitik; Internationaler Zahlungsverkehr; China; Deutschland